The use of nano-silicon carbide and nickel as catalyst in magnesium hydrides (MgH2) for hydrogen storage material application. (27th June 2018) - Jalil, Zulkarnain; Rahwanto, Adi; Ismail, Ismail; Sofyan, Hizir; Handoko, Erfan
Abstract: Magnesium (Mg) is currently known as one of the potential candidates for hydrogen absorbent material because theoretically, it has the ability to absorb hydrogen in large quantities of 7.6 wt%. However, the kinetic reaction of Mg is very slow; to absorb hydrogen takes 60 min with high operating temperature (>400 °C). Therefore, we have studied MgH2 -Ni-SiC-based storage system. The objective of this study is to improve the hydrogen desorption temperature and the hydrogen desorption capacity. The material preparation was done through mechanical alloying technique. In this method, the milling of the material was carried out within 5 h, 10 h and 15 h, with the ratio of the ball to powder, was 10:1 with the catalyst by 5 wt% and 10 wt% SiC. The results from XRD measurements revealed that the sample was successfully reduced to a nanocrystal scale. The phase emerging from the XRD observation is the phase MgH2 as the main phase and followed by Ni and SiC phase as the minor phase. Our SEM observation showed the irregular particle shape, the particle size in the sample is not homogeneous because of the agglomeration effect and coldwelding that causes the particle size to look larger. Based on the observation with DSC, the temperature obtained in the samples milled 10 h with catalyst 5 wt% SiC was 365 °C.